Efektivitas Pelayanan Kesehatan Melalui Electronic Government (Studi Kasus Pada Elektronik Sistem Kesehatan Lamongan "eSikla" di Puskesmas Deket Kecamatan Deket Kabupaten Lamongan) - Takharus Awal, Annisa Zahra; Noviyanti (Jurnal Inovasi Administrasi Negara Terapan (Inovant), 2023)
The purpose of this research is to analyze, and describe the effectiveness of health services through Electronic Health Lamongan (eSikla) at Puskesmas Deket. Electronic Health System Lamongan (eSikla) is a health information system developed to assist officers at each health center in Lamongan Regency, including the Deket Health Center, Deket District, Lamongan Regency. Data collection techniques used in this research include: interviews, observations, and documentation with purposive sampling technique where the research subjects in this study consisted of: eSikla program managers at the Lamongan Regency Health Office, Deket Puskesmas officers and Deket Puskesmas visitors. The data sources used are primary and secondary data sources with data analysis techniques including: data reduction, data presentation and conclusion drawing. This type of research is descriptive qualitative research with five indicators of effectiveness from Siagian as a theoretical basis, while the five indicators include: Human resources (HR), Funds, Facilities and infrastructure, Quantity and Quality and also Time. The results of the research show that health services through the Electronic Health System Lamongan "eSikla" at Puskesmas Deket Deket District, Lamongan Regency are still not effective. It is because of the five indicators put forward by Siagian, four of them are still not effective with the following description: Human resource indicators are less effective because not all officers can operate eSikla via computer. Fund indicators are also less effective due to the lack of funds or budget for updating or improving the quality of eSikla applications and server maintenance, facilities and infrastructure can be said to be effective because they are in accordance with the provisions of the Lamongan District Health Office, quality and quantity are also less effective because there are several obstacles related to the quality of the eSikla application, and time indicator is also not effective because implementation is often delayed.